Synthesis of silver nanoparticles via green approach using fruit extract of cupressus sempervirens L. and their antimicrobial evaluation - BHAWNA PAWAR; DEVENDRA SINGH NEGI (International Journal of Pharma and Bio Sciences, 2017)
In this study, silver nanoparticles have been synthesized using extract of Cupressus sempervirens fruit in aquous solution at room temperature. The fruit extract was able to reduce Ag+ to Ag0 and stabilized the nanoparticles. Different physico-chemical techniques including UV-Vis spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) with EDX were used for the characterization of biosynthesized silver nanoparticles obtained. The surface resonance band appeared at 450 nm is an evidence for formation of AgNPs. The XRD pattern showed the characteristic Bragg peaks of (111), (200), (220) and (311) facets of the face centre cubic (fcc) silver nanoparticles and confirmed that these nanoparticles are crystalline in nature. SEM micrograph showed that the synthesized Ag-NPs have spherical shape. HRTEM analysis showed particles with an average size of 29 nm. The silver nanoparticles possess significant antimicrobial potential against B.cereus and K. pneumoniae.